Procedure For Issuing Outward Manifest And Its Obstacles In Sea Transportation At PT. Admiral Lines Belawan - Shelly Octavani Agustie; Dirhamsyah Dirhamsyah; Yuna Sutria; Fadiyah Hani Sabila (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2023)
To find out more closely how the company PT Admiral Lines Belawan Branch, carrying out shipping activities in the issuance of Outward Manifest in the Customs online system, this aims to carry out responsibilities in submitting cargo reporting documents to parties that are truly related and responsible. As for the completeness of customs documents to support and expedite the Outward Manifest issuance procedure. as for the obstacles in the Outward Manifest issuance process that make it difficult to issue the Ouward Manifest, which the company can overcome seriously so that the company does not experience losses caused by a staff in submitting online data. With the Manifest Module online system, it is easier to manage Outward Manifest documents that train staff to be more thorough. This paper uses 2 (two) types of research methods, namely: the Field Observation method (Flied Reseach), interviews with employees and the Heritage Study Method (Library Reseach), namely taking data from library books.